Defining reflective practice from the Indonesian novice EFL teachers' perspective. Issue 4 (4th July 2022) - Derinalp, Pelin
ABSTRACT: Educational researchers have long attempted to define reflective practice. More than a century after the term was first introduced to the education field, there is still no consensus regarding its definition. This article suggests that although it is important to provide the practitioners with a comprehensive definition, it is not less important to investigate how the practitioners understand and define the concept. Therefore, this study attempts to provide empirical knowledge regarding how the practitioners conceptualise reflective practice. The participants of this study are six Indonesian novice English as a Foreign Language (EFL) teachers working at junior and senior high school levels in West Java, Indonesia. This study employs qualitative research methods and collects data through interviews. Thematic analysis has been adopted in order to analyse the data. The findings suggest that the participants understood the term reflective practice as a problem-solving strategy. In this regard, an activity for sharing knowledge, a flashback process for improving the teaching practices and a tool for professional development were the themes that were emerged from the data analysis. In order for practitioners to develop a full picture of the term, teacher education and training programs were invited to offer reflective practice as a separate module.